Doing justice for victims of violent crime in the European Union - Reflections on findings from a research project conducted by the European Union Agency for Fundamental Rights - Huxtable, Holly (International journal of comparative and applied criminal justice, 2021)
When it comes to defining the victim’s position in criminal justice systems, different approaches are adopted accross Europe including the adversarial procedure of common law countries that does not allow victims a role other than that of a witness, the French civil party system and the German model of the victim acting as joint prosecutor. While it is often the differences between these systems that are highlighted, this article stresses a profound commonality . Namely, that all models constitute variants of an orthodox, state-centred paradigm conceiving of criminal justice as a matter between the state and the defendant, where the state enforces the right of the collective polity to punish the offender. In this paradigm the victim essentially remains a witness supporting the state in prosecuting and convicting the offender - a role that fails to recognise the victim’s human rights and dignity. Evidence to support this claim is drawn from field research conducted in 2017 by the European Union Agency for Fundamental Rights (FRA). 1